EVALUATION OF THE ANTI-CATARACT POTENTIAL OF TINOSPORA CORDIFOLIA & PHYLLANTHUS EMBLICA IN AN IN VITRO SUGAR INDUCED CATARACTERIC LENS ORGAN CULTURE MODEL - KALEKAR SA,; MUNSHI RP,; KULKARNI DK, (International Journal of Pharma and Bio Sciences, 2014)
The present study was conducted to evaluate the in vitro anti-cataract potential of Tinospora cordifolia (Tc) and Phyllanthus emblica (Pe). Aldose Reductase Inhibitory (ARI) activity was evaluated using the method of Kinoshita et al. Only that concentration of plant extracts demonstrating maximum ARI activity was evaluated for anti-cataract and anti-oxidant potential using an in vitro sugar induced cataracteric lens organ culture model. Lens parameters evaluated included morphological variation, aldose reductase (AR) activity, Total Protein content and anti-oxidant enzymes viz., catalase and Superoxide Dismutase. Quercetin, a pure flavonoid was used as a positive control. Both Tc and Pe demonstrated dose dependent inhibition of AR with maximum activity at 100µg/ml. Loss of lens transparency, increased AR activity, decrease in soluble and total protein content was observed in diabetic lenses as compared to normal lenses. The diabetic conditions augmented anti-oxidant enzymes indicating oxidative stress. Supplementation with Tc & Pe decreased AR levels, increased levels of total and soluble proteins significantly with a decrease in catalase and superoxide dismutase. These results were comparable to quercetin. The results suggest that these plants have the potential to arrest the progression of cataract which is mediated by their anti-oxidant activity.